Classical and fractal models of chalcogenide glasses viscoelasticity - Horvat, A. A.; Molnar , A. A.; Minkovych, V. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2026)
The creep and mechanical stress relaxation in As–Se glasses at various temperatures were investigated experimentally, and the behavior of parameters that describe elastic properties and internal friction was analyzed within the framework of the classical standard models of solids and of the Burgers model. The theoretical basis for the description of viscoelastic phenomena in solids, in particular glassy materials, using the fractal Scott–Blair element is considered, and a mixed model incorporating of the Maxwell and Scott–Blair elements was proposed. A comparison of the correspondence between the experimental results and the parameters of the Burgers model and the mixed classical-fractal model was carried out. It was shown that the proposed mixed model takes into account the elastic and residual plastic deformation, as well as the power law dependence of the viscoelasticity.